Black-Box Testing : Analisis Kualitas Aplikasi Source Code Bank Programming - Ismail, Ismail; Efendi, Jalisal (KITA Institut, 2021)
The Source Code Bank Programming application that the researchers built uses Borland Delphi which functions to support software learning activities and as a reference for software developers, especially the Delphi programming language. In the process of developing Source Code Bank Programming is still in the prototype stage and further development is still being carried out so that it can be competitively competitive in the world. It is necessary to do various evaluations of the quality of the application in order to match the expectations of the user, one of which is to analyze the quality of the application using the Black-Box Testing method. Testing the Black-Box Source Code Bank Programming uses 3 methods, namely; 1) Graph-based testing, 2) Equivalence Partitioning, and 3) Boundary Value Analysis. The research results show that graph testing, equivalence partitioning, and boundary value analysis will be able to help the process of making test cases and make testing simpler, There are errors in testing and are included in the defect-list, the test results also show that the fulfillment of user needs for public users with a value 0.90, user registers/member with a value of 1.00, students with a value of 0.90, lecturers with a value of 0.82 and admin with a value of 0.84 are classified as good because the degree of value in each user module is greater than 0.8.